The Mechanisms of DNA Replication - Stuart, David (IntechOpen, 2013)
DNA replication is a fundamental part of the life cycle of all organisms. Not surprisingly many aspects of this process display profound conservation across organisms in all domains of life. The chapters in this volume outline and review the current state of knowledge on several key aspects of the DNA replication process. This is a critical process in both normal growth and development and in relation to a broad variety of pathological conditions including cancer. The reader will be provided with new insights into the initiation, regulation, and progression of DNA replication as well as a collection of thought provoking questions and summaries to direct future investigations.